Basic Life Support (Bhd) Training To Increase The Life Expectancy Of Sudden Cardiac Arrest Victims And Training On The Role Of Erythrocytes In The Respiratory System - rahmatullah, widia; Sari, Ana Dewi Lukita; Handyani, Reska (Jurnal Abdimas Saintika, 2024)
In the United States, around 436.852 adults in 2020 experienced cardiac arrest outside the hospital. Cardiopulmonary resuscitation (CPR) given immediately to someone with cardiac arrest can increase the chances of life expectancy. Cardiovascular disease is the number one cause of death in the world. In Indonesia, there is a shift in diseases from infectious diseases to non-communicable diseases, including heart and blood vessel diseases. According to Riskesdas in 2018, the incidence of heart disease is increasing in Indonesia from year to year, with 15 out of 1000 people or around 2.784.064 individuals in Indonesia suffering from heart disease. Sudden heart attacks can occur anywhere and at any time, can even occur at a young age, and can cause cardiac arrest. The pattern of handling cardiac arrest events in the family shows that the patient's family does not understand the emergency handling of cardiac arrest, where the BHD does not only call the hospital or be taken to the hospital, adjust the position, use ointment and loosen clothes. The target outcome is that students are able to apply the results of BHD training to be applied directly in the community if they find a victim who is unconscious, does not respond to pain stimuli, stops breathing and has no pulse in the carotid artery due to sudden cardiac arrest. Community service plans by providing BHD training to students at Binatama Monjali Vocational School, Sleman Yogyakarta. The training method uses phantom dolls and ambubags for BHD simulation, where students can carry out BHD training independently after receiving training on the correct BHD steps from the instructor.